RETRACTED: How Traumatic Violence Permanently Changes Shopping Behavior - Sigirci, Ozge; Rockmore, Marc; Wansink, Brian (Frontiers in Psychology, 2016)
Traumatic experiences – such as combat, living in a conflict country or war-torn nation, or experience a violent crimes or natural disasters – change social relationships and may also influence a life-time of consumer relationships with brands and shopping. Our focus on this previously overlooked area is centered on an analysis of the long-term shopping habits 355 combat veterans. We show that those who experienced heavy trauma (e.g., heavy combat) exhibited similar disconnection from brands as others have experienced in social relationships. They became more transactional in that they were more open to switching brands, to trying new products, and buying the least expensive alternative (p<0.01). In contrast, those who had experienced a light trauma were more influenced by ads and more open to buying brands even when they cost more (p<0.00). Trauma, such as combat, may change one’s decision horizon. Functionality and price become more important, which is consistent with the idea that they are more focused on the present moment than on building on the past or saving for the future.